ANALISIS MOTIVASI DAN MASA KERJA DALAM MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN (Studi Pada UD. Fajar Samudra Kabupaten Sumbawa) - Haryadi, Wahyu; Yopi, Lisa (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to analyze motivation and work period in improving work productivity of employees at UD. Fajar Samudra, Sumbawa District. The type of this study was associative research which aims to examine the effect of work motivation (X1) and work period (X2) on work productivity of employees at UD. Fajar Samudra, Sumbawa District (Y). The type of this study was associative research. The type of data used was quantitative data collected directly by researchers from research respondents using a research instrument in the form of a questionnaire. The respondents in this study were 40 employees of UD. Fajar Samudra, Sumbawa Regency, who were selected using saturated sampling techniques or census sampling. The data analysis tools using multiple linear regression analysis techniques, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and coefficient of determination testing (R2). The results of this study showed that work motivation (X1) and work period (X2) had a positive and significant effect on work productivity of employees at UD. Fajar Samudra, Sumbawa District (Y), both partially and simultaneously. The percentage contribution of work motivation and work period in effecting work productivity of employees at UD. Fajar Samudra, Sumbawa District was 88.5%, while the remaining of 11.5% was effected by other variables not examined in this study, such as education level, skills, discipline, attitude, work ethic, salary, health, technology, management, and opportunities for achievement.